2011
DOI: 10.1073/pnas.1109632108
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric cancer cell division regulated by AKT

Abstract: Human tumors often contain slowly proliferating cancer cells that resist treatment, but we do not know precisely how these cells arise. We show that rapidly proliferating cancer cells can divide asymmetrically to produce slowly proliferating "G0-like" progeny that are enriched following chemotherapy in breast cancer patients. Asymmetric cancer cell division results from asymmetric suppression of AKT/PKB kinase signaling in one daughter cell during telophase of mitosis. Moreover, inhibition of AKT signaling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 35 publications
9
121
1
1
Order By: Relevance
“…CICs in colon, breast, and ovaries have been shown to demonstrate the ability to maintain a quiescent state to evade therapy (46)(47)(48). In addition, Dey-Guha and colleagues (49) report that rapidly proliferating cancer cells can produce "G 0 -like" progeny through asymmetric division, which are enriched following chemotherapy in breast cancer. These G 0 phase cells show lower intracellular ROS level and exhibit suppressing AKT expression.…”
Section: Discussionmentioning
confidence: 99%
“…CICs in colon, breast, and ovaries have been shown to demonstrate the ability to maintain a quiescent state to evade therapy (46)(47)(48). In addition, Dey-Guha and colleagues (49) report that rapidly proliferating cancer cells can produce "G 0 -like" progeny through asymmetric division, which are enriched following chemotherapy in breast cancer. These G 0 phase cells show lower intracellular ROS level and exhibit suppressing AKT expression.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested a causal role for HES1 in the indirect regulation of AKT by Notch1. Further, HES1 contributes to establishment and maintenance of a quiescent phenotype (52), characterized by elevated HES1 and decreased AKT phosphorylation (53). Again, this suggests that HES1 is involved in AKT regulation.…”
Section: Pp2a Dephosphorylation or Whether This Is Mediated By A Downmentioning
confidence: 97%
“…27 Recent articles have demonstrated that even established cancer cell lines are not homogeneous, and identified rare, slowly cycling subpopulations in lung, melanoma, breast, and colon cancer cell lines. 22,[28][29][30] During our manuscript preparation, subpopulations of HCC827 cells with a quiescence-like state that resist EGFR TKIs have been reported to be highly susceptible to ABT-737, the predecessor of ABT-263. 29 Moreover, a report showed that HDAC inhibitors synergistically enhanced the levels of EGFR TKI-induced apoptosis in EGFR-mutant lung adenocarcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%